Hak Khuluk Perempuan dalam Perspektif Fikih dan Keadilan Gender - Fitriyani, Fitriyani (Tasyri' : Journal of Islamic Law, 2025)
This paper aims to explore the right of khuluk for women in the perspective of jurisprudence and gender justice. The main issues studied include: 1) What are the rights of women in the view of fiqh? and 2) How are women's khuluk rights reviewed from a gender perspective? This study uses a library research method by utilizing books, journal articles, and previous research reports, and is categorized as normative legal research that is analyzed descriptively. The results of the study show that the right of khuluk in the context of fiqh is a manifestation of gender equality in marriage relationships. If the husband has the right to divorce his wife through talaq, then the wife also has the right to "redeem" her husband through khuluk. Furthermore, the increase in divorce cases is influenced by several factors, including recurring conflicts, increasing women's awareness of their rights in the household, rejection of unfair treatment, economic independence, and a deeper understanding of religion, including regarding the provision of triple talaq. When women feel that triple talaq has been imposed by their husbands, they believe that religion forbids them to stay together. As a solution, efforts are needed to improve the quality of marriage advice. The advice should not only be entertaining for the bride-to-be, but also touch on substantial aspects, such as the importance of maintaining, caring for, and maintaining a harmonious marriage.